Case report: Echinococcus multilocularis infection in a dog showing gastrointestinal signs in Hokkaido, Japan - Kida, Izumi; Hayashi, Naoki; Yokoyama, Nozomu; Nagata, Noriyuki; Sasaoka, Kazuyoshi; Sasaki, Noboru; Morishita, Keitaro; Nakamura, Kensuke; Kouguchi, Hirokazu; Yagi, Kinpei; Nakao, Ryo; Takiguchi, Mitsuyoshi; et al. (Frontiers in Veterinary Science, 2024)
Echinococcus multilocularis is a cestode that causes human alveolar echinococcosis, a lethal zoonotic disease distributed in the northern hemisphere. The life cycle of this parasite is maintained in nature by voles as intermediate hosts and foxes as definitive hosts in Hokkaido, Japan. Although dogs are also susceptible to the parasite, the infection has been considered typically asymptomatic. We report the detection of E. multilocularis eggs in the diarrheal feces of a dog with chronic gastrointestinal signs, which disappeared after anthelmintic treatment. The mitochondrial genome sequence constructed by sequencing of the overlapping PCRs using DNA from the eggs was identical to the most predominant haplotype previously reported in red foxes in Hokkaido. This case highlights that Echinococcus infection should be considered as a differential diagnosis for diarrheal dogs in the disease endemic areas. Further efforts are needed to accumulate parasite genotypes in domestic dogs as well as humans to assess the risk of human infection from dogs.